PERSUASIVE-PARTICIPATORY COMMUNICATION AND THE SUSTAINABILITY OF WORSHIP PRACTICES: THE ROLE OF RELIGIOUS LEADERS IN A LOCAL MUSLIM COMMUNITY - Darul Naad; Abdullah; Efi Brata Madya (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
This study investigates the communication model employed by religious leaders to sustain consistent worship practices among community members in Sekerak Subdistrict, Aceh Tamiang Regency, Indonesia. Using a descriptive qualitative design, the study explores communication patterns, message-delivery strategies, congregational responses, and factors shaping the effectiveness of religious guidance. Data were collected through in-depth interviews with religious leaders, mosque and prayer-room administrators, community figures, and active congregants, complemented by direct observation and documentation. Data were analyzed using an interactive process of reduction, display, and conclusion drawing, with credibility ensured through source and methodological triangulation.The findings reveal an integrated persuasive-participatory communication model combining interpersonal, emotional, dialogical, and exemplary approaches. Two-way communication was particularly salient, enabling congregants to raise questions, express concerns, and discuss barriers to worship. Religious leaders reinforced commitment through accessible language, gentle persuasion, repeated motivational messages, personal engagement, emotional support, and role modelling. Effectiveness was strengthened by leader credibility, family involvement, supportive religious environments, and face-to-face interaction, but constrained by work and economic pressures, health conditions, weak spiritual motivation, social influences, and limited use of digital media.The study concludes that persuasive-participatory communication grounded in interpersonal closeness and exemplary conduct can strengthen spiritual awareness, worship discipline, and continuity. The findings extend persuasive-participatory communication as a framework for understanding sustained religious practice and highlight the need for dialogical guidance, stronger family and institutional involvement, and context-appropriate digital strategies.